Ice-source heat pump for residential heating: A case study on energy storage and pipeline repurposing in the UK - Ramin Mehdipour; Seamus Garvey; Bruno Cardenas; Zahra Baniamerian; Christopher J. Wood (Case Studies in Thermal Engineering)
Transitioning from natural gas to cleaner heating methods is crucial for reducing carbon emissions. Heat pumps, which extract heat from air, water, or geothermal sources, offer an efficient alternative but significantly increase peak electricity demand, particularly in cold climates. This study introduces an innovative ice-source heat pump system that utilizes pipelines for water circulation, reducing installation complexity, operational costs, and energy consumption. The proposed system draws energy from both the electrical grid and pipelines, optimizing supply and reducing reliance on electricity during peak hours. This research concerns the feasibility of repurposing gas pipelines for heat pump operation and their energy transmission capacity in a post-gas era.A typical UK residential unit in Nottingham's climate was modelled, revealing that heat pumps create two consumption peaks compared to one with gas heating. Peak electricity demand for air-source, ice-source, and water-source heat pumps was found to be 2.84, 2.70, and 2.56 times higher, respectively. While the ice-source heat pump performs between air- and water-source systems in electricity consumption, its significantly lower water demand enables better integration with existing pipelines. Additionally, phase change material (PCM) energy storage was explored to mitigate peak demand. Optimizing storage tank sizes and heat pump capacities reduced peak electricity consumption for the ice-source heat pump from 2.65 kW to 1.57 kW (40.75 %). The results show that repurposing existing gas pipelines could supply 39.66 % of the energy demand of current gas network consumers, making it a highly successful solution for non-fuel-based, low-temperature heat pump systems.